Factors associated with change in radiographic damage scores in gout: a prospective observational study. Issue 12 (24th February 2016) - Eason, Alastair; House, Meaghan E; Vincent, Zoe; Knight, Julie; Tan, Paul; Horne, Anne; Gamble, Gregory D; Doyle, Anthony J; Taylor, William J; Dalbeth, Nicola
Abstract : Background/aims: Radiographic damage is frequently observed in patients with longstanding gout. The aim of this prospective observational study was to determine factors associated with change in radiographic damage scores in gout. Methods: People with gout and disease duration <10 years were recruited into this prospective observational study. At the baseline visit, structured assessment was undertaken in 290 participants including detailed clinical examination and plain radiographs (XR) of the hands and feet. Participants were invited to attend a further study visit with repeat XR 3 years after the baseline visit. XR were scored for erosion and joint space narrowing according to the gout-modified Sharp/van der Heijde XR damage score. Results: Age, subcutaneous tophus count and tender joint count were independently associated with XR damage score at the baseline visit. Paired serial XR were available for 140 participants. In stepwise linear regression analysis, change in total damage score over 3 years was positively associated with change in subcutaneous tophus count and baseline XR damage score, and inversely associated with baseline subcutaneous tophus count (model R 2 =0.39, p<0.001). Change in subcutaneous tophus count contributed most to the change in erosion score (partial R 2 change=0.31, p<0.001), and baseline XR damage score contributed most to the change in narrowing score (partial R 2 change=0.31, p<0.001). Conclusions: Development of new subcutaneous tophi and baseline radiographic damage are associated with progressive joint damage scores in people with gout. These data provide further evidence that the tophus plays a central role in bone erosion in gout.